2015
DOI: 10.1590/1809-4430-eng.agric.v35n2p215-229/2015
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do efeito do estresse hídrico no crescimento de cultivares de cana-de-açúcar usando um sistema automático de fertirrigação

Abstract: O objetivo desta pesquisa foi identificar o efeito de diferentes níveis de estresse hídrico no crescimento das cultivares RB92579, RB855453, RB867515 e RB928064, utilizando um sistema automático de controle dos eventos de fertirrigação, durante o período de formação da cana-de- -açúcar. No período experimental, as plantas foram submetidas a períodos alternados de estresse e de reposição hídrica, por meio de fertirrigações periódicas, cujos limites do potencial matricial de água (Y) foram aqui denominados, para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
1
5
0
1
Order By: Relevance
“…m -2 . The dynamics of sugarcane growth and production in this study corroborate those found by Silva et al (2012a) and Silva et al (2014b), Batista et al (2015), Brunini & Turco (2016) and Oliveira & Braga (2019).…”
Section: Resultssupporting
confidence: 89%
“…m -2 . The dynamics of sugarcane growth and production in this study corroborate those found by Silva et al (2012a) and Silva et al (2014b), Batista et al (2015), Brunini & Turco (2016) and Oliveira & Braga (2019).…”
Section: Resultssupporting
confidence: 89%
“…The 3 dS m -1 value of the nutrient solution used in the cultivation of sugarcane was based on the studies of Trentin et al (2011), Boehringer et al (2013 and Batista et al (2015), and the amounts of NaCl in studies carried out with the aim of evaluating the effect of salinity on sugarcane growth (Plaut et al, 2000;Patade et al, 2011;Willadino et al, 2011;Simões et al, 2016). The EC monitoring was performed manually with a portable conductivity meter (CDH-42 model, Omega, Stamford, CT, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The measurements of the meteorological variables in the growing environment were carried out by four electronic sensors installed in a structure constructed from PVC pipes, connections with 50 mm diameter and white coloration ( Figure 1D), as used by Batista et al (2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Water stress causes a reduction in carbon dioxide assimilation rates, in leaf area size, in transpiration and growth rate, in plant water potential and stomatal opening (Rao et al, 2005;Gouvêa, 2008), in addition to a decrease in the stalk final height of sugarcane (Batista et al, 2015). Temperature is another extremely important climatic element in the production of sugarcane, acting directly on the maturation process, in which the plants respond to the thermal amplitude for the change from vegetative to reproductive stage (Doorenbos & Kassam, 1979).…”
Section: Introductionmentioning
confidence: 99%